Identifying factors influencing the leadership performance of Saudi's healthcare sector - Algarni, Namshan A.; Patrick, McLaughlin; Ahmed, Al-Ashaab; Hamad, Rashid (IBIMA, 2018)
The purpose of this article is to identify the aspects that relate to performance level; including enablers and inhibitors that influence leadership performance in the healthcare sector of the Kingdom of Saudi Arabia (KSA). A grounded research methodology and an action research approach that was ‘issue focused’ were used to gain the perceptions of the participants from the organisational culture as empirical data. The overall trends observed in the collected data emphasize the important role of culture in shaping performance level. In addition, the domination of factors related to the national culture and Islamic values has appeared the greatest factor affecting leaders' decisions; it also forms their relations with subordinates as well as their commitment to the organization. Viewed through this study, the effect of culture aspects on the performance level in this important sector can be understood and new and integrated solutions to overcome potential negative outcomes. Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to test the proposed propositions further. The paper discusses the implications of the study findings for healthcare sector managers in different levels. This paper fulfils an identified need to study how culture can influence workforce practices in healthcare organizations and to what extent can that affect the quality of services delivered to the patients.
Keywords: Healthcare sector; Saudi Arabia; culture; Leadership performance